2019
DOI: 10.1186/s12879-019-3722-z
|View full text |Cite
|
Sign up to set email alerts
|

Cold type autoimmune hemolytic anemia- a rare manifestation of infectious mononucleosis; serum ferritin as an important biomarker

Abstract: BackgroundInfectious mononucleosis is one of the main manifestations of Epstein – Barr virus, which is characterized by fever, tonsillar-pharyngitis, lymphadenopathy and atypical lymphocytes. Although 60% of patients with IMN develop cold type antibodies, clinically significant hemolytic anemia with a high ferritin level is very rare and validity of serum ferritin as an important biomarker has not been used frequently.Case presentation18-year-old girl presented with fever, malaise and sore throat with asymptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…His calculated HScore put him at a moderate probability of having reactive HLH. Because EBV-induced infectious mononucleosis and hemolytic anemia elevate ferritin levels [29], an acute CMV monolike illness with hemolytic anemia may do the same. Our patient's CD25 level was not in a range typically observed in HLH cases.…”
Section: Discussionmentioning
confidence: 99%
“…His calculated HScore put him at a moderate probability of having reactive HLH. Because EBV-induced infectious mononucleosis and hemolytic anemia elevate ferritin levels [29], an acute CMV monolike illness with hemolytic anemia may do the same. Our patient's CD25 level was not in a range typically observed in HLH cases.…”
Section: Discussionmentioning
confidence: 99%
“…Although the pathogenesis of EBV-induced AIHA is poorly understood, proposed mechanisms include the initial formation of IgM antibodies to EBV during the B-cell proliferation and polyclonal expansion phase that later contributes to molecular mimicry. 11 IgM antibodies cross-react with RBC antigens forming antigen-antibody complexes that activate the complement pathway, specifically C3b attaching to the RBC membrane. 11,12 In cold temperatures, IgM antibody also attaches to the RBC membrane to cause intravascular hemolysis, while in warm temperatures, the IgM antibody dissociates from RBC membrane and C3b remains, eventually causing extravascular hemolysis via the reticuloendothelial system.…”
Section: Discussionmentioning
confidence: 99%
“…11 IgM antibodies cross-react with RBC antigens forming antigen-antibody complexes that activate the complement pathway, specifically C3b attaching to the RBC membrane. 11,12 In cold temperatures, IgM antibody also attaches to the RBC membrane to cause intravascular hemolysis, while in warm temperatures, the IgM antibody dissociates from RBC membrane and C3b remains, eventually causing extravascular hemolysis via the reticuloendothelial system. 11,12 The elevated levels of circulating IgG, IgA, and IgM prior to IVIG treatment in this patient, showing the substantial lymphocyte proliferation from EBV infection, support this theory that overwhelming polyclonal expansion may cause AIHA as well as multiple false-positive serum markers of infection and autoimmune antibodies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High levels of serum glutamic pyruvic transaminase (SGPT) and serum glutamic oxaloacetic transaminase (SGOT) in infected individuals may indicate EBV-induced liver injury [8,9]. A study case reported high serum levels of ferritin and lactate dehydrogenase (LDH) in an 18 years old girl carrier of EBV-related infectious mononucleosis [10]. The girl was also a carrier of autoimmune hemolytic anemia, which could be caused by the EBV infection.…”
Section: Introductionmentioning
confidence: 99%